Predictors of Employee Turnover Intention in Micro-Scale MSMEs: An Exploratory Sequential Study - Muhammad Irfan Maulana Bima; Nurul Husna (Penerbit Goodwood, 2025)
Purpose: This study aims to explore the factors that predict the emergence of employee turnover intention, particularly among micro-scale MSMEs employees in Makassar, Indonesia. Methodology/approach: This study employs an exploratory sequential, mixed-method approach. The qualitative stage was carried out by interviewing seven respondents, and the quantitative stage was carried out on 101 micro-scale MSMEs employees in Makassar using a survey method. Results/findings: The findings indicate that employees’ desire for self-development and work comfort positively and significantly affect turnover intention. Meanwhile, organizational policy and salary were found to have no significant effect on employees’ turnover intentions. Conclusions: This study concludes that work comfort and employees’ desire to develop themselves are key predictors of turnover intention among micro-scale MSMEs employees in Makassar. Limitations: The limitation of this study lies in the depth of the interviews in the qualitative stage, which could be further expanded to gain more comprehensive insights into the predictors of employee turnover intention. Contributions: This study identifies predictors of employee turnover intention in the MSME context using a mixed-method approach that integrates respondents’ experiences with quantitative analysis, providing a more comprehensive understanding of the issue.